DETERMINATION OF PURCHASING DECISIONS AND CUSTOMER SATISFACTION: ANALYSIS OF SERVICE QUALITY AND PRODUCT QUALITY (MARKETING MANAGEMENT LITERATURE REVIEW) - Wydyanto Wydyanto; Ridho Rafqi Ilhamalimy (Dinasti Publisher, 2021)
The purpose of writing Literature Review Papers is to determine the effect of variable product quality and service quality on purchasing decisions and customer satisfaction. With qualitative methods and Library Research. The results showed that product quality effect on purchasing decisions, product quality effect on customer satisfaction, service quality effect on purchasing decisions, service quality effect on customer satisfaction and purchasing decisions effect on customer satisfaction.